The Effect of Applying the Brainstorming Method on Results Studying Social Sciences Subjects - Sandi, Sandi; Azis, Emmi; Yanti, Asia; Syamsurianto, Syamsurianto; Sahiruddin, Sahiruddin; Yusuf, Yusuf (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to analyze the effect of applying the brainstorming method on learning outcomes in social studies subjects. This research is quantitative research and is included in the One Group Pretest–Posttest type of experimental research. The population and sample for this study were all students at MTs Az-Zahra, a total of 26 people consisting of 23 men and 3 women. Data were analyzed using inferential analysis t-test. The research results show that there is a real difference between economic learning outcomes in the pre-test and post-test data, so it is concluded that H1 is accepted and H0 is rejected, which shows that the application of the Brainstorming method is effective in improving learning outcomes.